Decision Support Systems the Selection of Outstanding Students Using Simple Additive Weighting (SAW) and Weighted Product (WP) Methods - Riki Riki; Mimi Yanti (bit-Tech, 2020)
Appreciation for outstanding students is one of the encouragement for students to continue to maintain and improve their achievements. Generally, the selection of outstanding students in every school still uses the report value as the reference. Currently the selection of outstanding students at SMP Strada Santa Maria 2 still using the report card value (academic) as a reference. In addition, the school does not have a system that helps the selection and processing process based on several criteria considered. Therefore a decision support system is needed in order to help overcome problems and accelerate the selection of outstanding students. In this decision support system uses the SAW method (Simple Additive Weighting) and WP (Weighted Product) and compares the two methods. The criteria used included the value of the average semester 1, the value of the average semester 2, the value of attitudes, absences, and activeness of extracurricular activities. The results of these calculation in the form of the final value of each method and form of ranking that will be recommended to assist the school in determining the outstanding students according to the required criteria. Based on the terms of execution time, the SAW method is slightly faster than the WP method and and in terms of the test results using RSD, the value generated from the WP method calculation is better than the value generated from the SAW method calculation, where the RSD value of the WP method is 14.74% and SAW is 10.46%.